False hyperchloraemia in a dog secondary to ingestion of horse feed supplemented with potassium bromide. Issue 8 (26th July 2013) - Peacock, RE; Smart, L
<x xml:space="preserve">Abstract</x> Background A dog was presented for acute abdominal distension after inadvertent access to a large amount of dry dog food and possibly horse feed consisting of chaff, pony cubes and vitamin, mineral and yeast supplements. Results A marked hyperchloraemia and decreased anion gap on blood electrolyte analysis prompted a review of the patient's history for potential ingestion of bromide. It was revealed that the horse feed was supplemented with potassium bromide. The serum bromide level was 23.6 mmol/L. The dog recovered uneventfully. Conclusion This case report highlights the importance of knowing common interferents of chemical analysis techniques.